Construction of magnetic-targeted and NIR irradiation-controlled drug delivery platform with Fe3O4@Au@SiO2 nanospheres. Issue 6 (15th April 2017) - Liu, Xiaolin; Tao, Yongxin; Mao, Huihui; Kong, Yong; Shen, Jian; Deng, Linhong; Yang, Linsong
Abstract: Near-infrared (NIR) light has great potential in biomedical applications due to its advantages of deep penetration depth and low photodamage to biological tissues. In this paper, we constructed a novel core-shell structured drug nanocarrier, Fe3 O4 @Au@SiO2, for the controlled delivery of etoposide (VP16), a chemotherapeutic drug for cancer patients. The novel core-shell structured drug delivery platform is composed of a mesoporous silica shell and a magnetic Fe3 O4 core using Au nanoparticles (AuNPs) as the interlayer, which is characterized by atomic force microscopy (AFM), X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, N2 adsorption/desorption isotherms and the magnetic measurements with vibrating-sample magnetometer (VSM). The synergistic effects of AuNPs, mesoporous silica and Fe3 O4 make the core-shell structured nanocomposites an excellent candidate for targeted and NIR light irradiation-controlled drug delivery. For the proposed nanocarrier of VP16, the mesopores in silica can enhance the encapsulation capacity of the nanocarrier and the AuNPs can effectively convert the NIR light into heat to speed up the drug deliver; meanwhile, the incorporation of Fe3 O4 with high magnetization to the drug delivery platform realize drug targeting under an applied external magnetic field.